Implementation of Legal Protection for Tourists in Rafting Activities at Alam Tirta Outbound Based on the Provisions of Law Number 10 of 2009: Implementasi Perlindungan Hukum Terhadap Wisatawan dalam Aktivitas Arung Jeram di Alam Tirta Outbound Berdasarkan Ketentuan Undang-Undang Nomor 10 Tahun 2009 - Arini, Ni Nyoman; Anggara, Gusti Made Dwi Candra; Putri, Ida Ayu Karina (Jurnal Ilmiah Hospitality Management, 2024)
This study analyzes the legal protection for tourists participating in rafting activities at Alam Tirta Outbound, in accordance with the provisions outlined in Law Number 10 of 2009 concerning Tourism. The research uses a normative juridical approach, with data collected through observation, interviews, and documentation, alongside qualitative analysis of relevant regulations. Adventure tourism, particularly rafting, involves inherent risks, making the protection of tourists a significant concern for operators.  The findings reveal that Alam Tirta Outbound complies with the applicable legal provisions by providing insurance protection for tourists, covering risks related to accidents during rafting. Additionally, the site has established clear medical handling procedures, including the availability of First Aid in Accident (P3K) equipment and access to nearby health facilities for swift responses to incidents. The management also enforces strict safety standards, including regular inspections of river conditions and rafting equipment. These measures demonstrate a high level of commitment to protecting tourists' rights and fulfilling legal obligations in managing risky tourism activities.  While the study confirms Alam Tirta Outbound’s compliance with legal requirements, it also highlights that gaps remain in broader enforcement, such as the need for more comprehensive tourist education on risks and rights. The urgency of the study lies in the necessity to ensure consistent enforcement of safety protocols across the industry. This research contributes to tourism law by identifying practical challenges in applying legal protections in adventure tourism, offering recommendations to enhance legal frameworks and improve safety standards for tourists.